KONSEP ILMU DALAM ISLAM DAN IMPLIKASINYA DALAM PRAKTIK KEPENDIDIKAN - Sarjuni, Sarjuni (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
Islam as a worldview has a different point of view from other religion and civilisation perspective to see the world. This point of view is reflected and accumulated in the key concept understood from the main Islamic teaching source, Al-Qur’an and Sunnah. For example, related to the concept of science in the western civilisation. The concept of science in Islam has an effect on the goal orientation of Islamic education, that is different from the goal orientation of the western education. These Islamic Education goal are: Producing human being, having a good moral value, who can put something based on the real honor, using the right ways to reach the correct goal, and struggling for something to reach the right goal. The concept of science in Islam has an orientation to curriculum and classroom learning process. The education curriculum has to be developed integrally. Integrate between fardhu ‘ain and fardhu kifayah science development. In addition, the implementation of this can be dinamic. In the learning process of courtesies related to the science, the courtecies of the relationship between teacher and student in the educative interaction has to be implemented.Keywords: The concept of science, courtecy, and education